Chemical monitoring strategy for the assessment of advanced water treatment plant performance - Drewes, J E (Water science and technology : a journal of the International Association on Water Pollution Research, 2011)
A pilot-scale plant was employed to validate the performance of a proposed full-scale advanced water treatment plant (AWTP) in Sydney, Australia. The primary aim of this study was to develop a chemical monitoring program that can demonstrate proper plant operation resulting in the removal of priority chemical constituents in the product water. The feed water quality to the pilot plant was tertiary-treated effluent from a wastewater treatment plant. The unit processes of the AWTP were comprised of an integrated membrane system (ultrafiltration, reverse osmosis) followed by final chlorination generating a water quality that does not present a source of human or environmental health concern. The chemical monitoring program was undertaken over 6 weeks during pilot plant operation and involved the quantitative analysis of pharmaceuticals and personal care products, steroidal hormones, industrial chemicals, pesticides, N-nitrosamines and halomethanes. The first phase consisted of baseline monitoring of target compounds to quantify influent concentrations in feed waters to the plant. This was followed by a period of validation monitoring utilising indicator chemicals and surrogate measures suitable to assess proper process performance at various stages of the AWTP. This effort was supported by challenge testing experiments to further validate removal of a series of indicator chemicals by reverse osmosis. This pilot-scale study demonstrated a simplified analytical approach that can be employed to assure proper operation of advanced water treatment processes and the absence of trace organic chemicals